A Comparison of Strategies to Improve Population Diets: Government Policy versus Education and Advice - Norman J. Temple (Journal of Nutrition and Metabolism)
Different strategies have been utilized in order to improve the healthiness of the population diet. Many interventions employ education, advice, and encouragement (EAE). Those interventions have been carried out in diverse settings and may achieve modest success; the estimated risk of cardiovascular disease is lowered by about 5–15%. An alternative strategy is action policies carried out by the governments. The removal of trans-fatty acids from food is a model for a successful action policy. Other action policies include requiring a substantial reduction in the amount of salt added to processed foods and ordering schools to cease supplying unhealthy food to students. Taxes and subsidies can be used to increase the price of unhealthy foods, such as sugar-rich foods, and reduce the price of healthy foods, such as fruit and vegetables. It is very probable that action policies are more effective than those based on EAE. They are also much more cost-effective.